Quadriceps Muscles O2 Extraction and EMG Breakpoints during a Ramp Incremental Test - Iannetta, Danilo; Qahtani, Ahmad; Millet, Guillaume Y.; Murias, Juan M. (Frontiers in Physiology, 2017)
Muscle deoxygenated breakpoint ([HHb]BP) has been found to be associated with other indices of exercise tolerance in the vastus lateralis (VL) muscle but not in the vastus medialis (VM) and rectus femoris (RF). Purpose: to investigate whether the [HHb]BP occurs also in the VM and RF muscles and whether or not it is associated with other physiological indices of exercise tolerance, such as the EMG threshold (EMGt) and the respiratory compensation point (RCP). Methods: 12 young endurance trained participants performed maximal ramp incremental tests (25-30 W·min-1 increments). Muscle oxygen extraction and activity as well as gas exchange parameters were measured. After accounting for the mean response time, the oxygen uptake (V̇O2) associated to the RCP, [HHb]BP, and the EMGt was determined. Results: peak power output (POpeak) was 359±48 W. Maximal V̇O2 (V̇O2max) was 3.87±0.46 L·min-1. The V̇O2 at the RCP was 3.39±0.41 L·min-1. The V̇O2 (L·min-1) corresponding to the [HHb]BP and EMGt were: 3.49±0.46 and 3.40±0.44; 3.44±0.61 and 3.43±0.49; 3.59±0.52 and 3.48±0.46 for VL, VM, and RF, respectively. Pearson’s correlation between these thresholds ranged from 0.90 to 0.97 (P <0.05). No difference was found for the absolute V̇O2 and the normalized PO (%) at which the thresholds occurred in all three muscles investigated (P >0.05). Although in eight out of twelve participants, the [HHb]BP in the RF led to a steeper increase instead of leading to a plateau-like response as observed in the VL and VM, the V̇O2 at the breakpoints still coincided with that at the RCP. Conclusions: this study demonstrated that local indices of exercise tolerance derived from different portions of the quadriceps are not different to the systemic index of the RCP.